Validation and cross-cultural adaptation of the Korean translation of the Achilles tendon Total Rupture Score - Young Hwan Park; Hyun Woo Cho; Jung Woo Choi; Hak Jun Kim (BMC Musculoskeletal Disorders, 2021)
Abstract Background The Achilles tendon Total Rupture Score (ATRS) is a widely used patient-reported outcome measure to assess clinical outcomes of Achilles tendon rupture, but it has not been validated in Korean yet. The purpose of this study was to translate the ATRS into Korean and evaluate its reliability and validity in a Korean population. Methods The ATRS was translated into Korean according to recommended guidelines for forward-backward translation. Thirty-eight patients who underwent surgical treatment for Achilles tendon rupture from 2017 to 2019 were enrolled. Reliability was evaluated by the intraclass correlation coefficient (ICC), standard error of measurement (SEM), and minimal detectable change (MDC). Construct validity was assessed with Spearman rank correlations with the Korean version of the Foot and Ankle Outcome Score (FAOS) and Numeric Rating Scale (NRS) for pain in daily activity. Results The Korean translation of the ATRS had excellent test-retest reliability (ICC = 0.84) and acceptable internal consistency (Cronbach’s alpha = 0.84). The SEM was 6.61, and the MDC was 18.32 at the individual level and 2.97 at the group level. The Korean translation of the ATRS was strongly correlated with the FASO (r = 0.88). Correlation with the NRS in daily activity (r = − 0.66) was moderate. Conclusion The Korean translation of the ATRS showed sufficient reliability and validity for use in the Korean population. Level of evidence II.